2015
DOI: 10.1007/s00127-015-1072-8
|View full text |Cite
|
Sign up to set email alerts
|

The Avon Longitudinal Study of Parents and Children (ALSPAC) birth cohort as a resource for studying psychopathology in childhood and adolescence: a summary of findings for depression and psychosis

Abstract: The ALSPAC birth cohort has provided important insights for our understanding of the aetiological mechanisms underlying depression and PEs. Future research could aim to incorporate measures of automatic psychological mechanisms to provide insights into the brain mechanisms that underlie these clinical phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 113 publications
(86 reference statements)
2
48
0
Order By: Relevance
“…Furthermore, parental separation can lead to residential moves, which for the children may entail entering a new school and having to make new friends in an already stressful situation [13]. Indeed, changing schools has been shown to be linked with an increased risk of adverse mental health [21]. Unsurprisingly, studies have shown that it is more common for individuals with separated parents to have moved during childhood [12, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, parental separation can lead to residential moves, which for the children may entail entering a new school and having to make new friends in an already stressful situation [13]. Indeed, changing schools has been shown to be linked with an increased risk of adverse mental health [21]. Unsurprisingly, studies have shown that it is more common for individuals with separated parents to have moved during childhood [12, 18].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of assessing functioning across this broader range of developmental domains is underscored by longitudinal prospective cohort investigations (e.g. Niarchou et al 2015; Poulton et al 2015), which demonstrate that early childhood difficulties in behavioural, emotional, social, cognitive and physical functioning are risk factors for a variety of adverse adolescent and adult outcomes beyond juvenile delinquency and adult offending, including mental and physical illnesses, social maladjustment, and poor educational and occupational outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…to account for attrition in cohort studies (Niarchou et al, 2015, Sterne et al, 2009 (Fagan, 2014, Niarchou et al, 2015. These findings, if replicated…”
mentioning
confidence: 62%